Eve's Diary, Part 1 - Twain, Mark, 1835-1910; Ralph, Lester (Salt Lake City, UT : Project Gutenberg, 2004)
"Eve's Diary, Part 1" by Mark Twain is a comic short story first published in 1905. Written as the diary of the biblical Eve, it chronicles her creation, discovery of Eden, and relationship with Adam through her own voice. Part of Twain's series on Adam and Eve, this story stands out for its appreciation of beauty and love. Believed to be a tribute to Twain's late wife Olivia, it concludes with Adam's poignant words at Eve's grave: "Wheresoever she was, there was Eden." (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Eve%27s_Diary
Release date is 2004-06-01
Produced by David Widger and Cindy Rosenthal
Keywords: Humorous stories; Diary fiction; Bible. Genesis -- History of Biblical events -- Fiction; Eve (Biblical figure) -- Fiction